Seismic Performance Evaluation of Raised Access Floor Systems Using the Shaking-Table Test - Kang, Jun Young; Cho, Bong Ho; Jung, Dam I. (International Journal of Steel Structures, 2024)
Raised access floor systems are used in facilities with underfloor air distribution or heavy equipment, such as telecommunication systems. However, the seismic performance of these systems must be evaluated to ensure the safety of occupants. Thus, this study evaluates the seismic performances of R-type access floor systems in general offices. To this end, shaking table tests were performed on three R-type access floor systems (Korean Standard, KS F 4760) according to the ICC-ES AC156 standard, with floor acceleration applied horizontally in one direction. Three systems were designed in which the specimens were connected to the floor using adhesives, anchor bolts, and a new connecting system. This study aimed to analyze the dynamic behavior of the three R-type access floor systems as a function of the connection method between the access floor and the slab. Moreover, the damage limit state was defined based on the performance level. Results revealed that the specimen RT (adhesive connection between the R-type access floor and slab) achieved a life safety level at spectral acceleration, whereas RT-PA (adhesive and partially anchor bolts connection between the R-type access floor and slab) and RT-F (rail-supported system connection between the R-type access floor and slab) secured an operational level.
Keywords: Access floor systems; Distribution equipment; Heavy equipment; Non-structural elements; OA floor; Raised access floor; Seismic Performance; Seismic performance evaluation; Shaking table tests; Underfloor air distributions; Non-structural element; O.A floor; Raised access floor; Seismic performance; Shaking table test